UNDANG-UNDANG MARIAGE POUR TOUSDAN HOMOFOBIA DI PRANCIS - Astrid Vionisa Casondra; Miranda, Airin (Universitas Hasanuddin, 2021)
France is one of the countries in the world that upholds individual freedom and equal rights for every citizen. The first policy related to the recognition of homosexuals in France was the PACS (Pacte Civil de Solidarité) which was inaugurated in 1999. Then the latest development, on May 18, 2013 finally legalized same-sex marriage in France, known as mariage pour tous. With the mariage pour tous law, homosexuals in France can legalize their relationship through the original marriage bond by the state. Homosexuals people hope that with this law, the negative view of French society towards homosexuals can be eliminated. By using qualitative methods and literature study techniques as well as analysis of critical discourse theory by Norman Faircglough (1995), the result of the study shows that after the marriage law was legalized, acts of violence and discrimination by homophobic people still continued to increase in France.